Functionalised Alkaline Earth Iodides from Grignard Synthons "PhAeI(thf)n" (Ae = Mg‐Ba). Issue 7 (18th January 2019) - de Bruin‐Dickason, Caspar N.; Deacon, Glen B.; Jones, Cameron; Junk, Peter C.; Wiecko, Michal
Abstract : Derivatisation of Grignard synthons "PhAeI(thf) n " (Ae = Mg‐Ba) prepared in situ from reactions of metal filings and iodobenzene provides a one‐pot synthesis of heteroleptic N donor alkaline earth iodide complexes. Protolysis of "PhAeI(thf) n " with 3, 5‐diphenylpyrazole (Ph2 pzH) yields pyrazolate complexes [Mg2 (µ‐Ph2 pz)2 (I)2 (thf)3 ] (1 ), [Ae(Ph2 pz)(I)(thf)4 ] (Ae = Ca (2 ), Sr (3 )), and [Ba2 (Ph2 pz)2 (µ‐I)2 (thf)8 ] (4 ). Addition of the Ae‐Ph moiety to carbodiimide MesN=C=NMes (Mes = 2, 4, 6‐(CH3 )3 C6 H2 ) gave a series of benzamidinate iodide complexes [Ca2 (MesN)2 CPh2 (µ‐I)2 (thf)4 ] (6), [Sr(MesN)2 CPh(I)(thf)4 ] (7 ), and [Ba(MesN)2 CPh(µ‐I)(thf)3 ∞ ] (8 ). By contrast a symmetrical magnesium complex [Mg(MesN)2 CPh2 (thf)] (5 ) was obtained by Schlenk redistribution. These syntheses proceed without pre‐activation of the metal for strontium and barium, and after activation with 2 mol‐% iodine for calcium. The heavy alkaline earth metal complexes are the first examples of heteroleptic halide pyrazolate or amidinate complexes for strontium and barium. Complexes 1, 3, 4 and 6–8 were characterised crystallographically, revealing diverse structural chemistry of heteroleptic amidinate and pyrazolate iodide complexes across the alkaline earth series. A highlight is [Ba(MesN)2 CPh(µ‐I)(thf)3 ]∞ (8 ) – an iodide bridged infinite 1‐D polymer. Abstract : Heavy Grignard reagents "PhAeI(thf) n " can be protolysed by pyrazoles to yield pyrazolate iodide complexes or add to carbodiimides to give benzamidinate iodide complexes. PhAeI(thf) n ' is straightforward to prepare and its derivatisation enables direct access to bifunctional alkaline earth complexes from the metal. X‐ray characterisation has enabled structural comparisons across the Ae series (Mg‐Ba) for new heteroleptic iodide complexes.